Estudo de raios cósmicos utilizando uma câmara de nuvens de baixo custo - Laganá, Caio [UNESP] (My University, 2011)
Using images from cosmic rays interactions obtained with a low cost cloud chamber, the main observed phenomena in such an experiment are presented, discussed and classified. © The Sociedade Brasileira de Física.
Cosmic ray study using a low cost cloud chamber
Keywords: Cloud chamber; Cosmic ray; Elementary particles